A Pulse Radiolysis Study of the Dynamics of Ascorbic Acid Free Radicals within a Liposomal Environment. Issue 14 (23rd July 2014) - Kobayashi, Kazuo; Seike, Yumiko; Saeki, Akinori; Kozawa, Takahiro; Takeuchi, Fusako; Tsubaki, Motonari
Abstract The dynamics of free‐radical species in a model cellular system are examined by measuring the formation and decay of ascorbate radicals within a liposome with pulse radiolysis techniques. Upon pulse radiolysis of an N2O‐saturated aqueous solution containing ascorbate‐loaded liposome vesicles, ascorbate radicals are formed by the reaction of OH. radicals with ascorbate in unilamellar vesicles exclusively, irrespective of the presence of vesicle lipids. The radicals are found to decay rapidly compared with the decay kinetics in an aqueous solution. The distinct radical reaction kinetics in the vesicles and in bulk solution are characterized, and the kinetic data are analyzed.